L’enseignement « traditionnel » dans l’Ouest saharien et ses références extérieures - Abdel Wedoud Ould Cheikh (Revue des Mondes Musulmans et de la Méditerranée)
This text presents an overview of the traditional educational resources available in the Moorish Sahara between the 16th and 21st centuries. After reviewing the social context and material conditions, the author presents a table of the subjects and textbooks around which this teaching was organized. Teaching methods and the body of works studied in the Western Sahara do not differ substantially from the practices and tools used in the Maghreb and in neighboring Sudano-Sahelian countries. The Malikism-ashʿarism-sufism triad provides the essential orientations. One could add less frequently used texts and texts devoted to the teaching of minor, non-religious disciplines (grammar, lexicography, logic, rhetoric, mathematics, astronomy, medicine…). It should be noted however, that from the 18th century onwards, the local production, generally prepared from glosses and commentaries on imported canonical works, began to be incorporated into the corpus of taught works.